Hominin hand bone fossils from Sterkfontein Caves, South Africa (1998–2003 excavations). Issue 118 (May 2018) - Pickering, Travis Rayne; Heaton, Jason L.; Clarke, Ron J.; Stratford, Dominic
Abstract: We describe eleven hominin metacarpals and phalanges recovered from Jacovec Cavern and Member 4 of the Sterkfontein Formation between 1998 and 2003. Collectively, the fossils date in excess of 2.0 Ma, and are probably attributable to Australopithecus africanus and/or Australopithecus prometheus . When combined with results of previous studies on Australopithecus postcranial functional morphology, the new data presented here suggest that at least some late Pliocene and/or early Pleistocene hominins from Sterkfontein were arboreally adept. This finding accords with the reconstruction of the site's >2.0 Ma catchment area as well-vegetated and containing significant woody components. In addition, most of the new specimens described here evince morphologies that indicate the hands from which they derived lacked complete modern humanlike manual dexterity, which is integral to the manufacture and use of intentionally shaped stone tools. The absence of lithic artifacts from both stratigraphic units from which the fossils were excavated is consistent with this conclusion.